Manajemen Keuangan Perusahaan Menurut Perspektif Grestenberg - Evy Latifah (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2022)
This research was conducted to describe and explain the steps of financial management from Grestenberg's point of view. The research was conducted qualitatively with a library study approach. Data collection techniques with documentation studies. Data processing techniques with reduction, data presentation and drawing conclusions. Data validity technique with source triangulation. The results of the research show that financial management is a way for companies to obtain, use and obtain funds for business activities. Financial management steps that can be taken: first, obtaining company funds by determining financial sources to sustain the company's life through borrowing, pawning securities, cooperation with companies and so on. Second, the use of funds by utilizing funds for the benefit of the company such as paying salaries, buying goods, paying rent and so on. Third, distribution of funds by channeling funds at all levels of management within the company.